Multiplex PCRs for Identification of Escherichia coli Virulence Genes - Pass, M. A. (American Society for Microbiology, 2000)
PCRs were developed to detect 11 Escherichia coli virulence genes. Primers amplified the respective genes without cross-reaction with other genes. Specificity was maintained in multiplex reactions; excellent amplification of target genes was possible with a minimum of four multiplex reactions. These reactions successfully identified genes in E. coli from the feces of four dogs.